CD161+CD4+ T cells are enriched in the liver during chronic hepatitis and associated with co-secretion of IL-22 and Interferon-gamma - Kang, Yu-Hoi; Seigel, Bianca; Bengsch, Bertram; Fleming, Vicki; Billerbeck, Eva; Simmons, Ruth; Walker, Lucy; Willberg, Chris; Barnes, Eleanor J.; Bhagwanani, Anisha; Oo, Ye; Blum, Hubert; et al. (Frontiers in Immunology, 2012)
Hepatitis C virus infection is a major cause of chronic liver disease. CD4+ T cells play a key role in disease outcome. However, the critical functions and associated phenotypes of intrahepatic CD4+ T cells are not well defined. We have previously shown that CD8+ T cells expressing the C type lectin CD161 are highly enriched in the human liver, especially during chronic hepatitis. These cells are associated with a type 17 differentiation pattern and express cytokines including IL-17A, IL-22 and IFNγ. We therefore analysed expression of CD161 on CD4+ T cells in blood and liver and addressed the relevant phenotype and functional capacity of these populations. We observed marked enrichment of CD161+CD4+ T cells in the liver during chronic hepatitis such that they are the dominant subtype (mean 55% of CD4+ T cells). IL-22 and IL-17 secreting CD4+ cells were readily found in the livers of HCV+ and NASH donors, although not enriched compared to blood. There was, however, specific enrichment of a novel subset of IL-22/IFN-γ dual secretors (p=0.02) compared to blood, a result reconfirmed with direct ex vivo analyses. These data indicate the dominance of CD161+ expressing lymphocyte populations within the hepatic infiltrate, associated with a distinct cytokine profile. Given their documented roles as antiviral and hepatoprotective cytokines respectively, the impact of co-secretion of IFNγ and IL-22 in the liver may be particularly significant.